2014
DOI: 10.1161/circresaha.114.301633
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 Controls the Proliferative, Migratory, and Inflammatory Phenotype of Pulmonary Vascular Fibroblasts

Abstract: Rationale Pulmonary hypertensive remodeling is characterized by excessive proliferation, migration, and proinflammatory activation of adventitial fibroblasts. In culture, fibroblasts maintain a similar activated phenotype. The mechanisms responsible for generation/maintenance of this phenotype remain unknown. Objective We hypothesized that aberrant expression of microRNA-124 (miR-124) regulates this activated fibroblast phenotype and sought to determine the signaling pathways through which miR-124 exerts eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
185
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(189 citation statements)
references
References 80 publications
3
185
0
1
Order By: Relevance
“…Elevated miR-145 expression was observed in primary PASMCs cultured from patients with PAH with loss-of-function BMPR2 mutations as well as in the lungs of BMPR2-deficient mice. Importantly, mice with genetic deletions of miR-145 exhibited protection against PH (28). Conversely, miR-140 has been implicated in the regulation of Smad ubiquitination regulatory factor 1 (SMURF1), an E3-ubiquitin protein ligase 1, that in turn modulates BMPR2 signaling and PAH in vivo (29).…”
Section: Metabolism and Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated miR-145 expression was observed in primary PASMCs cultured from patients with PAH with loss-of-function BMPR2 mutations as well as in the lungs of BMPR2-deficient mice. Importantly, mice with genetic deletions of miR-145 exhibited protection against PH (28). Conversely, miR-140 has been implicated in the regulation of Smad ubiquitination regulatory factor 1 (SMURF1), an E3-ubiquitin protein ligase 1, that in turn modulates BMPR2 signaling and PAH in vivo (29).…”
Section: Metabolism and Proliferationmentioning
confidence: 99%
“…In vitro gain-and loss-of-function experiments revealed that decreased miR-124 in PAAFs from patients with PAH led to increased proliferation and migration through modulating the polypyrimidine tract-binding protein 1 (PTPB1) and subsequent inhibition of the cell cycle (28). Separately, the miR-130/301 family has been found to modulate extracellular matrix stiffening in PAAFs (31) via interfacing with the transcriptional coactivators YAP (Yes-associated protein) and TAZ (transcriptional coactivator with PDZ-binding motif).…”
Section: Metabolism and Proliferationmentioning
confidence: 99%
“…4,5 During the remodeling, pulmonary adventitial fibroblasts (PAFs) are highly activated and undergo phenotype switch characterized by excessive proliferation, migratory, and inflammatory activity. 6,7 Therefore, inhibition of the aberrant activation of PAFs may reverse the remodeling process of pulmonary vascular adventitia and have therapeutic potential for HPH. 8 Increasing evidence shows that miRNAs, especially miR-29 family members, participate in the development of organ fibrosis via regulating the activation of fibroblasts.…”
mentioning
confidence: 99%
“…[9][10][11] Downregulation of miR-29 underlies transforming growth factor-β-mediated pulmonary fibrosis, and overexpression of miR-29 inhibits bleomycin-induced pulmonary fibrosis. 12 Although PAFs in HPH undergo the similar activated phenotype to that in lung fibrosis, 6 the role of miR-29 family member in the hypoxia-induced activation of PAFs and the development of HPH is not known. On the other hand, hypoxia-inducible factor-1α (HIF-1α), a key transcription factor mediating cellular response to hypoxia, and Smad3, which can inhibit miR-29 expression in organ fibrosis, are interdependent in hypoxia.…”
mentioning
confidence: 99%
“…82 More recently, the efficacy of HDAC inhibitors in PH fibroblasts was linked to induction of miR-124. 86 miR-124 had previously been shown to have antiproliferative action in glioblastoma cells. 87 In cultured PH fibroblasts (both human and bovine), miR-124 expression was found to be dramatically downregulated.…”
Section: Mechanisms Of Action Of Hdac Inhibitors In Phmentioning
confidence: 99%